Former Oesing Kitchen Colonial Building in Banyuwangi as Urban Heritage - Miskawi (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Banyuwangi Regency is rich in pen-colonial legacy. Colonial remains can still be found in several parts of the city, but quite a few have changed form, even looking different from their original state. One of the buildings is the former Oesing kitchen. The research aims to explore the facade-forming and space-forming elements in the former Oesing Kitchen, Banyuwangi, and the condition of the former Oesing building after restoration. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The colonial buildings selected as study cases were carried out using purposive sampling techniques using several criteria. Data analysis was carried out inductively with greater emphasis on historical meaning and value. The results of the observations are a way to explain and conclude the two elements that form the architectural character of these colonial buildings. The research results show that the former Oesing kitchen building has an architectural character that can be determined from the windows, entrance, roof, and walls. Meanwhile, other characters can be determined from the basic plan and shape of the building. Apart from that, there are historical supporting objects such as chimneys, old tombs, nagabulan, and agricultural buildings.